The Impact of Crowdfunding on Social Entrepreneurship: A Bibliometric Analysis - Mora-Cruz, Alexandra (2025)
Crowdfunding has established itself as a key tool for financing social entrepreneurship, offering an effective alternative that allows entrepreneurs to access the resources needed to carry out their projects. The primary objective of this research is to analyze the scientific production that may influence future studies on the impact of crowdfunding on social entrepreneurship. This study explores the influence of crowdfunding in this area through a systematic literature review and bibliometric analysis. The study is based on the analysis of articles published in the last 10 years in the Scopus and Web of Science databases related to crowdfunding and social entrepreneurship. After applying specific criteria to select the most closely related articles, 38 were chosen. The scientific production was evaluated using the Bibliometrix tool, allowing for a detailed analysis of various relevant indicators and variables. The results of this study highlight the importance of crowdfunding in promoting sustainable businesses driven by and for the community. Additionally, future lines of research are identified, particularly focusing on the role of technology, the measurement of social impact, and legal frameworks in the evolution of crowdfunding applied to social entrepreneurship. This research offers a clear view of how crowdfunding drives social entrepreneurship and supports investment decision-making, becoming of great interest to researchers and entrepreneurs in the field of social financing.